PELATIHAN PENGGUNAAN APLIKASI DIGITAL PADA MASYARAKAT DESA GUMANTAR KABUPATEN LOMBOK UTARA GUNA MENDUKUNG PROGRAM DESA DIGITAL - Arik Aranta; I Gede Pasek Suta Wijaya; Ramaditia Dwiyansaputra; Ario Yudo Husodo; Gibran Satya Nugraha; Fitri Bimantoro; Muhammad Daden Kasandi Putra Wesa (Universitas Mataram, 2023)
Digital villages represent a rapidly evolving phenomenon that has become highly significant in the modern era. The Faculty of Engineering at Mataram University has taken proactive steps to address this pressing issue by accelerating the implementation of digital villages in Gumantar Village, North Lombok Regency, with a specific focus on the Lembah Telaga farming group. This community engagement effort is concentrated on two key aspects: the development of internet connectivity infrastructure and the enhancement of internet literacy, particularly in the context of agriculture. The primary objective of this project is to provide much-needed internet access to the community and to equip individuals with the skills necessary to swiftly engage in activities and information exchange. This is particularly crucial in the agricultural sector, which heavily relies on fast and accurate access to information. Remarkably, all participants, including residents and members of the Lembah Telaga farming group who own smartphones, have successfully achieved full proficiency in utilizing the newly installed internet infrastructure. Telkomsel Orbit Star was chosen as the optimal device to meet the unique needs of North Lombok Regency, specifically in Gumantar Village. This infrastructure is expected to become a valuable asset in supporting the digitalization and advancement of the Lembah Telaga farming group in the future. The success of this project is evident in the improved capabilities of the community to access various internet platforms such as YouTube, Google, and Instagram. With the newfound knowledge they have gained, the residents of Gumantar Village now have unlimited internet access through Telkomsel orbital internet device installed at the Lembah Telaga farming group training facility. This significantly facilitates their ability to access agricultural information on the internet, thereby enhancing their potential and prospects in an increasingly digitally connected agricultural landscape.